Conformation and Catalytic Properties Studies of Candida rugosa Lip7 via Enantioselective Esterification of Ibuprofen in Organic Solvents and Ionic Liquids - Xiang Li; Shuangshuang Huang; Li Xu; Yunjun Yan (The Scientific World Journal)
Enantioselective esterification of ibuprofen was conducted to evaluate the enzyme activity and ees of lipase from Candida rugosa (CRL7) in ten conventional organic solvents and three ionic liquids. Different alcohols were tested for selecting the most suitable acyl acceptor due to the fact that the structure of alcohols (branch and length of carbon chains; location of –OH functional group) could affect the enzyme activity and ees. The results of alcohol and solvent selection revealed that 1-isooctanol and isooctane were the best substrate and reaction medium, respectively, because of the highest enzyme activity and ees. Compared with the control, conformational studies via FT-IR indicate that the variations of CRL7’s secondary structure elements are probably responsible for the differences of enzyme activity and ees in the organic solvents and ionic liquids. Moreover, the effects of reaction parameters, such as molar ratio, water content, temperature, and reaction time, in the selected reaction medium, were also examined.